Neural nets and surroundings 22nd Italian Workshop on Neural Nets, WIRN 2012, May 17 - 19, Vietri sul Mare, Salerno, Italy - Apolloni, Bruno, 1946- (Smart innovation, systems, and technologies, 2013)
This volume collects a selection of contributions which has been presented at the 22nd Italian Workshop on Neural Networks, the yearly meeting of the Italian Society for Neural Networks (SIREN). The conference was held in Italy, Vietri sul Mare (Salerno), during May 17-19, 2012. The annual meeting of SIREN is sponsored by International Neural Network Society (INNS), European Neural Network Society (ENNS) and IEEE Computational Intelligence Society (CIS)